GOODS PRINTING RESERVATION SYSTEM IN PT. PERKASA CAHAYA BUNDA USING VISUAL BASIC 6.0 - Dian Oktaviana (Jurnal Sistem Informasi, 2005)
This Scientific writing is about how to make a reservation system that was computerized by using Visual Basic 6.0. In scientific writing is also a database using Microsoft Access 2000 which has been integrated in visual basic 6.0 program, and also using Crystal Report 4.6 to display the report be printed. Scientific writing is also equipped with Flow of Document (FOD), Data Flow Diagram (DFD), Entity Relationship Diagram (ERD) and also normalization of the system are made. Existing programs in this system consists of the main menu that displays the Input menu is used to enter the order data and data products, Menu List is used to view the entire data and also orders the goods data, reports menu is used to display and print the monthly and annual reports, print invoices payment. This system aims to replace is made the old system which still manual with the new system was computerized, with the hope that this new system could make the company's performance to be better, especially in the marketing division that handles transaction orders.